Impaired Respiratory Function among Workers and Residents Exposed to an Organic Fertilizer Plant in Swani, Libya - Ali Dow,; Salim Ataeb, (AlQalam Journal of Medical and Applied Sciences, 2025)
Occupational exposure to air pollutants in fertilizer production poses a significant risk to respiratory health. This study assessed the respiratory efficiency of workers and residents near an organic fertilizer factory in the Swani area, Libya. A cross-sectional study was conducted with 235 male participants, aged 20-59 years, who were free of pre-existing respiratory or cardiac diseases. Subjects were divided into three groups: Group I (control, unexposed to major air pollution sources), Group II (workers directly exposed at the factory), and Group III (residents living nearby). The primary measure of respiratory function was the Peak Expiratory Flow Rate (PEFR). Data were analyzed using paired t-tests with SPSS-PC software. Forty-seven patients completed the follow-up protocol. A statistically significant reduction in VAS scores for nasal obstruction was observed at all postoperative time points compared to preoperative baselines (p<0.05). Symptomatic improvement commenced at the first postoperative week and was sustained through the 3-month assessment. While a minor recrudescence in symptoms was noted at the 6-month follow-up, the mean VAS score remained significantly improved over the preoperative value (p < 0.05). Overall, 89.4% of patients reported satisfactory symptomatic improvement over the 6-month study period. Workers and residents in proximity to the fertilizer factory in Libya are at an elevated risk of developing occupationally and environmentally related pulmonary impairments. These findings underscore the urgent need for enhanced control measures for vapors and gases at existing sites.